Politics, unemployment, and the enforcement of immigration law - Michael D. Makowsky; Thomas Stratmann (Center for Economic Studies and ifo Institute (CESifo), 2012)
Immigration control-related audits and their resulting sanctions are not solely determined by impartial enforcement of laws and regulations. They are also determined by the incentives faced by vote-maximizing congressmen, agents acting on their behalf, and workers likely to compete with immigrants in the local labor market. In this paper we test to what extent congressional oversight, i.e., legislative involvement, determines the bureaucratic immigration enforcement process. We examine the determinants of decisions made at each stage of regulatory enforcement for over 40,000 audits from 1990 to 2000. This includes an analysis of the determinants of whether a firm is 1) found in violation, 2) whether a warning or fine issued, 3) the size of the fine issued, and 4) how much of dollar reduction fined employers were able to negotiate after the fact. Consistent with the hypothesis that locals will provide more tips to the enforcement agency when unemployment is high, we find that the number of audits conducted grows with increased local unemployment. We also find that a congressman's party affiliation and its interaction with committee membership, party rank, and party majority status, as well as firm size and local union membership, correlate to bureaucratic decisions made at every stage of immigration enforcement.
Keywords: J61; K31; K42; 330; immigration; enforcement; political economy